2017
DOI: 10.1080/08870446.2017.1368511
|View full text |Cite
|
Sign up to set email alerts
|

Increasing physical activity through an Internet-based motivational intervention supported by pedometers in a sample of sedentary students: A randomised controlled trial

Abstract: This study shows the effectiveness of a self-administered IMI using pedometers in increasing PA and enjoyment, and the effectiveness of the IMI alone in changing different theoretical constructs related to the PA behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(81 citation statements)
references
References 39 publications
0
59
0
1
Order By: Relevance
“…Six studies were conducted in North America [38][39][40][41][42][43], five studies in Europe [44][45][46][47][48], one in Singapore [49] and one in New Zealand [50]. Sample sizes ranged from 15 [39] to 1519 [43], and the duration of interventions ranged from three weeks [46] to three years [45]. Further study characteristics are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were conducted in North America [38][39][40][41][42][43], five studies in Europe [44][45][46][47][48], one in Singapore [49] and one in New Zealand [50]. Sample sizes ranged from 15 [39] to 1519 [43], and the duration of interventions ranged from three weeks [46] to three years [45]. Further study characteristics are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The analysis of study quality revealed one study classified as strong [43], nine studies as moderate [39][40][41][42][44][45][46]48,50] and three studies as weak [38,47,49]. Due to missing documentation of confounders prior to the intervention or insufficient control of confounders, most of the studies resulted in a weak rating.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations